2015
DOI: 10.1363/47e5715
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Exploration of Sexual Experiences Among Adults on the Autism Spectrum: Implications for Sex Education

Abstract: Individuals on the autism spectrum would benefit from sex education that normalizes differences (e.g., in identities and experiences of sexuality), is offered throughout young adulthood, addresses disability-relevant sensory and communication needs, and includes practicing neurotypical sociosexual norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 34 publications
2
52
1
Order By: Relevance
“…It might be possible that a small minority exists that does not, or to a lesser degree, experience sexual arousal. Feelings of asexuality in adults with ASD have also been previously reported [ 10 , 38 40 ].…”
Section: Discussionmentioning
confidence: 69%
“…It might be possible that a small minority exists that does not, or to a lesser degree, experience sexual arousal. Feelings of asexuality in adults with ASD have also been previously reported [ 10 , 38 40 ].…”
Section: Discussionmentioning
confidence: 69%
“…Here this would mean producing qualitative research into autistic peoples' sexual and intimate lives without taking as a starting point an assumption of deficit, or certain non-autistic expectations of what counts as 'sexual'. This call for qualitative research soliciting the views and experiences of autistic people has been made for decades [46,47]. With the increasing interest in studying sexuality generally [48], and a growing understanding that the complexity of human sexuality and gender identity is not currently captured by traditional research methods and categories [40,49,50] perhaps the time is now ripe to carry out this research.…”
Section: Resultsmentioning
confidence: 99%
“…Ordinary spontaneous playful and loving sex is absolutely wonderful!' 45 A possibly higher proportion of autistic people identifying as LGBTQ is explained either through differences between autistic and non-autistic sexualities, 46 or with different ways of talking about or practicing sexuality in relation to different social norms. Autistic people may have difficulties with hiding non-conformative sexualites, don't think that it may be inappropriate to talk about it in certain contexts, 47 or are less likely to supress 'deviant' sexual preferences as a result of social pressure than non-autistic people.…”
Section: Non-normative Sexualitymentioning
confidence: 99%
“…First, findings relating to sexual orientation (feeling attraction to someone of the same sex, the other sex or both sexes) in adolescents and adults with ASD varied. Some studies found similar proportions of same sex attraction or experience (5–10%) among participants with ASD and TD peers (Dewinter et al 2015 ; Fernandes et al 2016 ), while other studies reported higher levels of non-heterosexual feelings and experiences in ASD (Barnett and Maticka-Tyndale 2015 ; Gilmour et al 2012 ; Strunz et al 2017 ) compared to the general population. In the US population (Copen et al 2016 ) 17.4% of girls and women, and 6.2% of boys and men (age 18–44) reported same-sex experiences at some point during their lifetime.…”
Section: Introductionmentioning
confidence: 97%